Peran Kecerdasan Buatan dalam Mengembangkan Kompetensi dan Meningkatkan Motivasi Belajar Mahasiswa - Praptodiyono, Supriyanto; Suryawijaya , Muhamad Rizki; A’Kaasyah , Sayyidina Nur (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2025)
Artificial intelligence (AI) plays a significant role in enhancing students' learning competencies and motivation, particularly in the field of informatics. This study aims to explore the types of AI most frequently used by students, their experiences in utilizing AI, and its impact on understanding the material, analytical skills, and programming abilities. A case study was conducted on students of the Informatics Study Program, Faculty of Engineering, Sultan Ageng Tirtayasa University, class of 2023. A qualitative method was applied with data triangulation through observation, interviews, and questionnaire surveys. The results showed that ChatGPT was the most widely used AI (68.42%), followed by Blackbox AI and Copilot, both of which were highly effective in simplifying coding and debugging processes. AI proved to enhance learning efficiency, provide quick solutions, broaden perspectives, and support mastery of algorithms and programming syntax. However, excessive dependence on this technology poses a risk of diminishing critical thinking skills and academic integrity. This study emphasizes the importance of digital literacy and ethical guidelines to ensure the wise use of AI, so that this technology can support learning without compromising the development of students' independent skills